Antifibrotic Effect of Combination of Nilotinib and Stem Cell-Conditioned Media on CCl4-Induced Liver Fibrosis. (3rd February 2020) - Shiha, Gamal; Nabil, Ahmed; Lotfy, Ahmed; Soliman, Reham; Hassan, Ayman A.; Ali, Islam S.; Gad, Doaa F.; Zahran, Faten
Abstract : Liver fibrosis is the excessive extracellular matrix accumulation of proteins, such as collagen, which follows the chronic liver diseases. Advanced liver fibrosis leads to cirrhosis and liver failure. Nilotinib is a second-generation tyrosine kinase inhibitor, which showed antifibrotic efficacy. Stem cell therapy still has some limitations such as oncogenesis, unexpected differentiation, and ethical consideration. Stem cells secrete cytokines and growth factors that showed paracrine-mediated antifibrotic and anti-inflammatory effects in vivo and in vitro. Thus, stem cell-conditioned medium (SC-CM), which contains the secretory proteins of stem cells, may have an antifibrotic role. This study was carried out to examine the antifibrotic effect of Nilotinib and stem cell exosomes on CCl4 -induced liver fibrosis in rats. Male Wistar rats were injected intraperitoneally with CCl4 twice a week for 9 weeks and given daily treatments of Nilotinib (20 mg/kg), stem cell exosomes (0.5 ml/rat), and the combination treatment of Nilotinib and stem cell exosomes during the last 5 weeks of CCl4 intoxication. Liver fibrosis and also antifibrotic efficacy of the treatments were estimated with liver function tests, oxidative stress parameters, apoptotic parameters, histopathological examination, and hydroxyproline contents. Results showed that the combination of Nilotinib and stem cell-conditioned media had more antifibrotic effects than each one alone (P value < 0.001).